Drying as a primary hydrological determinant of biodiversity in river systems: a broad‐scale analysis. Issue 4 (5th April 2016) - Leigh, Catherine; Datry, Thibault
Abstract : Determining and understanding relationships between biodiversity and hydrology is a critical goal in ecology, particularly given biodiversity in the freshwater realm is in crisis. Despite the prevalence of rivers experiencing natural drying disturbances (which we collectively refer to as intermittent rivers), and projections of increased frequency and duration of drying events, the importance of drying relative to other flow‐related determinants of river biodiversity remains understudied. We assessed the influence of drying on alpha‐ and beta‐diversity using discharge and macroinvertebrate data collated from Australia and southwest Europe over broad spatial and temporal scales, providing information on current and past drying events, and combining a wide variety of flow metrics. We found clear evidence that drying acts as a strong environmental filter and is a primary hydrological determinant of alpha‐diversity; even when considering both intermittent and perennial rivers, drying‐event conditions were its most important predictors. Macroinvertebrate richness declined with increasing durations of drying over the long‐term (Australia) and recent (Australia and southwest Europe) history of river discharge, and with decreasing predictability of event timing (Australia). Our analysis also revealed that: responses can be taxon specific due to variation in traits of resistance and resilience to drying; some taxa may respond just as or more strongly to variation in other discharge components (e.g. high‐ or low‐flow events) than to drying; and together these phenomena may result in differing community‐level responses within and across regions. Patterns of beta‐diversity across the wide biogeographical range of our study suggested that convergent and divergent niche‐selection processes may act in combination on aquatic communities of rivers experiencing drying disturbances. However, strong ability to disperse by flight (not by water) weakened beta‐diversity patterning among rivers. Our findings can be used to improve understanding of biodiversity organisation in disturbed systems, notably in those with dendritic features, including intermittent rivers.